The Influence of K-Pop Girl Group “TWICE” as Brand Ambassador of Scarlett Whitening on Purchase Intention (Journal of Business and Management, 2022)
Abstract. The tight competition, makes personal care industry must have an effort in maintaining the company. The marketing strategy that can be carried out is to use brand ambassador to improve brand image, brand trust and of course to increase the purchase intention of its customers for the brand/product. If a company chooses the wrong brand ambassador, it will have a negative impact on the company's image. This study aims to determine the effect of Twice as a brand ambassador on Scarlett Whitening's brand image, brand trust, and purchase intention. The data for this study were collected through an online survey with 255 respondents. With the criteria of being 12-27 years old this year, knowing the brand/product of Scarlett Whitening, and knowing Twice as the brand ambassador of Scarlett Whitening. The data collected was then analyzed by PLS-SEM to determine the relationship between research variables. This study shows that brand ambassadors have a significant effect on brand image and brand trust. Purchase intention can be significantly influenced by brand image, and brand trust. The results of the mediation state that brand image and brand trust can fully mediate brand ambassadors on purchase intentions. The recommendation given is to do marketing in the form of advertisements, by featuring Twice as the Brand Ambassador of Scarlett Whitening to be better known by customers.Keyword: Twice, Scarlett Whitening, Brand, Brand Ambassador, Brand Image, Brand Trust, Purchase Intention